Subcutaneously Placed Breast Implants after a Skin-Sparing Mastectomy: Do We Always Need ADM?. Issue 7 (July 2017) - Singla, Apresh; Singla, Animesh; Lai, Eric; Caminer, David
Abstract : Background: Immediate breast reconstruction is an acceptable treatment option after mastectomy for prophylaxis of early breast cancer. Different options exist for implant placement, incision technique, patient suitability, and institutional experience. This article is a case series exploring the feasibility and outcomes of patients undergoing immediate breast reconstruction using skin-sparing mastectomy without mesh or acellular dermal matrix (ADM) and with a vertical inframammary incision. Methods: A single-institution retrospective analysis was performed for all patients who underwent immediate single-stage reconstruction with subcutaneous silicon implants without ADM between 2009 and 2014 inclusive. Patient, operative and treatment variables were extracted. All patients with viable mastectomy skin flaps intraoperatively and at least 5 mm of subcutaneous tissue were eligible except for patients who were deemed too slim by the senior surgeon preoperatively and thus at risk of implant visibility or skin rippling. Results: There were 26 patients (bilateral n = 12 and unilateral n = 14) eligible for analysis, with a median long-term follow-up of 51.5 months. The majority of complications were classified as minor affecting 46.2% of the cohort (n = 12). There were 20 episodes of complications overall. The most frequent episodes were contour defects (x = 5), minor seroma (x = 4), and malrotation and minor infection (x = 3). There was 1 episode of capsular contracture. Conclusion: Skin-sparing mastectomy with immediate subcutaneous silicon implant reconstruction with a vertical incision and without the need for mesh or ADM is an acceptable and safe treatment option. Accurate patient selection and skin flap viability is the key to achieving optimal outcomes with this approach.